1983
DOI: 10.1227/00006123-198301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Change in Cerebral Blood Flow during the First Three Weeks after Subarachnoid Hemorrhage

Abstract: Cerebral blood flow (CBF) was estimated from each cerebral hemisphere by the 133Xe inhalation method. Daily estimates were made during the first 3 weeks after subarachnoid hemorrhage (1265 studies in 116 patients). Some of the patients were taking adrenergic blocking drugs (propranolol and phentolamine), others were taking tranexamic acid, and the rest were taking no drugs. CBF was also studied in 67 normal subjects. The resting CBF was related inversely to age not only for normal subjects but also for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In summary, the present study indicates that rats subjected to the dual-hemorrhage model of SAH exhibit biphasic changes in CBF and the diameter of cerebral arteries that closely mimic the time course and magnitude of the response previously reported in humans (30,54) and the dual-hemorrhage dog and monkey models of SAH (29,52). Acute blockade of the synthesis of 20-HETE fully reversed cerebral vasospasm in this model.…”
Section: Role Of 20-hete In Delayed Vasospasm In Ratssupporting
confidence: 85%
See 1 more Smart Citation
“…In summary, the present study indicates that rats subjected to the dual-hemorrhage model of SAH exhibit biphasic changes in CBF and the diameter of cerebral arteries that closely mimic the time course and magnitude of the response previously reported in humans (30,54) and the dual-hemorrhage dog and monkey models of SAH (29,52). Acute blockade of the synthesis of 20-HETE fully reversed cerebral vasospasm in this model.…”
Section: Role Of 20-hete In Delayed Vasospasm In Ratssupporting
confidence: 85%
“…Previous studies have documented that there are biphasic changes in the diameter of cerebral arteries in humans after SAH (30,54). The acute phase lasts several hours.…”
Section: Discussionmentioning
confidence: 98%
“…High intracranial pressure and vasospasm lead to cerebral ischemia with concomitant neuronal damage in various neuronal territories involved in the processing of sensor and motor information [6]. A variety of clinical and experimental studies demonstrated a close correlation between the severity of bleeding, the extent of the ischemic damage and the clinical status of the patient [4,5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the initial severity of the hemorrhage and CBF reduction during the early SAH period are the major determinants of imminent morbidity and mortality (3,17). A more pronounced initial decrease in CBF has also been found in patients with a higher Hunt and Hess grade (5,12,19). Acute hypoperfusion is caused by various cellular and structural changes, but the theory that acute vasospasms are a major factor has gained widespread acceptance (20).…”
Section: Hemodynamic Changes After Subarachnoid Hemorrhagementioning
confidence: 99%